2017
DOI: 10.1371/journal.pgen.1006511
|View full text |Cite
|
Sign up to set email alerts
|

Anillin Phosphorylation Controls Timely Membrane Association and Successful Cytokinesis

Abstract: During cytokinesis, a contractile ring generates the constricting force to divide a cell into two daughters. This ring is composed of filamentous actin and the motor protein myosin, along with additional structural and regulatory proteins, including anillin. Anillin is a required scaffold protein that links the actomyosin ring to membrane and its organizer, RhoA. However, the molecular basis for timely action of anillin at cytokinesis remains obscure. Here, we find that phosphorylation regulates efficient recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
(58 reference statements)
2
28
0
1
Order By: Relevance
“…And Anillin, a phylogenetically conserved protein, is the essential component that plays the scaffold protein role and links the actomyosin ring to the membrane and RhoA, which is a pivotal effector directing the localization of the contractile actomyosin ring [ 23 ]. In other words, dysfunction of Anillin could impair the efficient integration of RhoA functions and leads to failure of cytokinesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…And Anillin, a phylogenetically conserved protein, is the essential component that plays the scaffold protein role and links the actomyosin ring to the membrane and RhoA, which is a pivotal effector directing the localization of the contractile actomyosin ring [ 23 ]. In other words, dysfunction of Anillin could impair the efficient integration of RhoA functions and leads to failure of cytokinesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This autoinhibition could ensure that anillin’s C-terminus has access to importin or microtubules only when RhoA-GTP levels increase during mitotic exit. A recent study showed that anillin is also regulated by phosphorylation, via a site that lies just N-terminal to the RBD ( Kim et al. , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was also underpinned by the evidence of phosphomimetic-mutant S635D, the negative charge of D at the 635 residues which partially recovered the localization. S635 phosphorylation helps ANLN improve the efficacy of the Rho integration with its upstream and downstream regulators, which contributes to the success of cytokinesis [58]. To date, the kinases that are responsible for S635 remain unidentified, so there is a need to determine which kinases are responsible for the phosphorylation at S635.…”
Section: Other Binding Partnersmentioning
confidence: 99%
“…CDK1 was found to interact with ANLN [56,57], and it is indicated that ANLN mobility is directly or indirectly regulated by CDK1 via phosphorylation [58]. The ANLN-actin-binding protein has been identified as being involved in PI3K/PTEN signaling, which is critical in cell life/death control [59].…”
Section: Other Binding Partnersmentioning
confidence: 99%